Prescription of EPs 7630 is associated with short- and long-term benefits in acute bronchitis: a real-world data analysis - Gillissen, Adrian; Reineke, Thorsten; Burkart, Martin; Funk, Petra; Adarkwah, Charles Christian; Kostev, Karel (Frontiers in Pharmacology, 2025)
IntroductionAcute bronchitis is caused by an infection of the lower respiratory tract, resulting in considerable distress of patients and substantial economic costs due to lost workdays. Although acute bronchitis is mostly caused by viruses, antibiotics are frequently used. The aim of this study was to evaluate whether a prescription of EPs 7630 for patients with acute bronchitis is associated with a lower recurrence rate of the disease or fewer complications, a reduced need for antibiotic therapy, or fewer lost workdays.MethodsA retrospective analysis was conducted using the IQVIA™ Disease Analyzer database, which contains information from nearly 3,000 office-based physicians, representing around 3%–5% of all German practices. We analyzed the rates of recurrence of acute bronchitis, antibiotic prescription, duration of sick leave, and incidence of complications (pneumonia, chronic bronchitis) with regard to their association with prescriptions of EPs 7630, ambroxol, acetylcysteine, or antibiotics for acute bronchitis.ResultsOf the 376,366 patients suffering from acute bronchitis between January 2005 and December 2022, 1,994 received prescription of EPs 7630, 14,952 ambroxol, 24,149 acetylcysteine, and 335,271 antibiotics. EPs 7630 prescription was associated with a significantly lower likelihood of re-consultation due to acute bronchitis within 365 days compared to ambroxol (HR: 0.74; 95% CI: 0.65–0.83), acetylcysteine (HR: 0.78; 95% CI: 0.69–0.88), and antibiotics (HR: 0.75; 95% CI: 0.67–0.85) (p < 0.001 each). The incidence of an antibiotic prescription following an initial EPs 7630 prescription was significantly lower compared to acetylcysteine (HR: 0.89; 95% CI: 0.81–0.98) (p = 0.020). EPs 7630 was also associated with a lower risk of pneumonia and chronic bronchitis and a lower proportion of patients with sick leave lasting >3 and ≥7 days, respectively, compared to the other prescription groups.ConclusionPrescribing EPs 7630 is associated with a lower incidence of disease recurrence and complications, a reduced need for antibiotic therapy, and a reduction in lost workdays. The results of this retrospective analysis thus emphasize the overall benefits of EPs 7630 as an effective treatment option for managing acute bronchitis.